GDF-15 contributes to proliferation and immune escape of malignant gliomas - Roth, Patrick; Junker, Markus; Tritschler, Isabel; Mittelbronn, Michel; Dombrowski, Yvonne; Breit, Samuel N.; Tabatabai, Ghazaleh; Wick, Wolfgang; Weller, Michael; Wischhusen, Jörg (Clinical cancer research, 2010)
Purpose: Growth and differentiation factor (GDF)-15 is a member of the transforming growth factor (TGF)-β family. GDF-15 is necessary for the maintenance of pregnancy but has also been linked to other physiologic and pathologic conditions.Experimental Design: The expression of GDF-15 in glioma cell lines was assessed by quantitative reverse transcriptase-PCR and immunoblot. GDF-15 levels in situ and in the peripheral blood of glioma patients were examined by immunohistochemistry and enzyme-linked immunosorbent assay, respectively. The effects of short hairpin RNA-mediated GDF-15 inhibition on proliferation and immunogenicity of SMA-560 glioma cells were investigated by [methyl-3H]thymidine incorporation and immune-mediated target cell lysis. The impact of GDF-15 on glioma growth in vivo was assessed in syngeneic mice.Results: GDF-15 is expressed by gliomas of different WHO grades as assessed by immunohistochemistry. The high expression of GDF-15 in tumor tissue translates into elevated GDF-15 serum levels in glioblastoma patients compared with healthy controls. GDF-15 mRNA and protein are also detectable in human and mouse glioma cells in vitro. Silencing of GDF-15 by RNA interference reduces the proliferation of malignant glioma cells. Immunologically, the depletion of glioma-derived GDF-15 enhances the susceptibility of mouse glioma cells towards syngeneic natural killer cells and splenocytes. This results in a reduced in vivo tumorigenicity and increased T-cell infiltration of GDF-15-deficient glioma cells in syngeneic mice.Conclusions: Although previous studies focusing on ectopic overexpression of GDF-15 have proposed unclear or antitumorigenic effects of GDF-15 in glioma cells, we here show that GDF-15 at endogenous levels contributes to proliferation and immune escape of malignant gliomas in an immunocompetent host. Clin Cancer Res; 16(15); 3851-9. ©2010 AACR.
Gesehen am 21.06.2023